Tracing of The Leachate in The Marine Medium - Balkis, N.; Aksu, A.; Ersan, M.S.; Muftuoglu, E.; Zeki, S.; Demir, V.; Taskin, O. (Asian Journal of Chemistry, 2010)
The leachate carried from the solid waste landfills constitutes a great proportion of the surface water pollution. Solid waste leachate includes much more pollution loads than the domestic and industrial wastewater. In this study, the analyses of the water samples taken from the rudder room, port and starboard engine departments of the Saricabey Sea Bus and the seawater are performed and a judgment is exposed if the pollution which was determined by the law enforcement agency was originated from this sea bus or not. The analyses were carried out by using the GC/MS (HP 6890 GC system/mass selective detector) instrument. Consequently, the solid waste leachate, which was carried to the marine media, is proved to be the origin of the mentioned pollution.